Caloric Restriction Alleviates CFA-Induced Inflammatory Pain via Elevating β-Hydroxybutyric Acid Expression and Restoring Autophagic Flux in the Spinal Cord - Liu, Chang; Zheng, Xiaoting; Liu, Lifang; Hu, Yun; Zhu, Qianyun; Zhang, Jiawei; Wang, Huan; Gu, Er-wei; Yang, Zhilai; Xu, Guanghong (Frontiers in Neuroscience, 2022)
Inflammatory pain is the most common type of pain in clinical practice. The currently available treatments are limited by their insufficient efficacy and side effects. Therefore, new ways to relieve inflammatory pain according to new mechanisms are urgently needed. Preclinical investigations have shown that CR (calorie restriction) has analgesic effects in neuropathic and cancer pain, but the effect of CR in chronic inflammatory pain remains unknown. During calorie restriction, autophagy, a lysosomal-dependent degradation process, can be activated to support cell survival. In this study, we investigated the analgesic effects of CR on CFA-induced inflammatory pain. The accumulation of LC3-II and p62 showed impaired autophagic flux in the ipsilateral spinal cord of mice with CFA-induced inflammatory pain. CR alleviated the mechanical allodynia and thermal hyperalgesia, and reduced the paw edema and pro-inflammatory factors after CFA administration. We then found that CR exerted the analgesic effect by restoring the autophagic flux in the spinal cord. With regard to the mechanisms underlying the analgesic effects of CR, the β-hydroxybutyric acid (BHB) was then studied. CR increased the BHB levels in the ipsilateral spinal cord. And exogenous BHB administration exerted the analgesic effect by restoring autophagic flux in the spinal cord of mice with CFA-induced inflammatory pain. Taken together, these results illustrated that CR relieved inflammatory pain via restoring autophagic flux in the spinal cord, and BHB controlled the benefits of CR, suggesting that CR or BHB might be a promising treatment for inflammatory pain.